2021
DOI: 10.1136/bmjopen-2021-052557
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations of housework with cognitive, physical and sensorimotor functions in younger and older community-dwelling adults: the Yishun Study

Abstract: ObjectivesRegular moderate-to-vigorous intensity recreational physical activity (PA) improves physical and cognitive functions. However, the age-associated relationships between non-recreational PA and functional ability remain less explored. We examined the associations between housework and functional health among younger and older Singaporean community-dwelling adults.DesignCross-sectional study.Setting and participantsYounger (<65 years, n=249) and older (≥65 years, n=240) community-dwelling adults were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…The distribution between domains was quite similar in 2000/2001. Results confirm recent research pointing to the often neglected importance of household work [ 5 , 14 ]. Findings further stress the importance of nature contact and interaction – possibly a cultural feature of Sweden [ 28 ] – as well as everyday walking activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The distribution between domains was quite similar in 2000/2001. Results confirm recent research pointing to the often neglected importance of household work [ 5 , 14 ]. Findings further stress the importance of nature contact and interaction – possibly a cultural feature of Sweden [ 28 ] – as well as everyday walking activity.…”
Section: Discussionsupporting
confidence: 89%
“…These are domains that to various degrees are the focus of health research, policy, and practice. Housework has recently received attention for making a significant contribution to MVPA among older adults [ 14 ], a contribution often neglected when not studying the entirety of everyday life and overlooking time spent in domestic (reproductive) work and obligations. For the same reason, we distinguish other household-related activities included in the maintenance and repair domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic activities such as housework is a form of physical activity which may provide benefits from less intensive and more sustainable regimens [ 14 ]. Promoting increased activities that fit into everyday life, including housework and home maintenance tasks, might increase physical activity adherence and improve population health, especially in older adults, as more people would be capable of meeting physical activity guidelines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review indicated that individuals had cognitive impairment during the first episode of depression and those with multiple episodes showed more severe cognitive impairment [ 36 ]. Physical activities were also found to be linked with higher cognitive performance, especially in attention and memory [ 37 ]. Age and gender were frequently identified as factors associated with cognitive decline [ 38 ].…”
Section: Discussionmentioning
confidence: 99%